ETOS KERJA MEMBANGUN KELUARGA SAKINAH PERSPEKTIF FUNGSIONALISME MALINOWSKI (Studi di Lembaga Dakwah Islam Indonesia Kota Kediri) - Arianto (Center for the Research and the Communicator Service of IAI Hasanuddin Pare-Kediri, 2021)
The essence of ethos is character or character. For Malinowski, culture is an instrument of the human way to solve life's problems more specifically in its environment (family), that is, an effort to fulfill its needs. The view of functionalism, religion functions as a controller of the individual's lust to do positive and valuable things that provide a good relationship between man and his God. Religiosity and work ethic of LDII citizens form a family of sakinah mawaddah wa rahmah with Tri success and six traits they have. This character is in line with the character of Toto Tasmara's Islamic work ethic. The results obtained from this study are that the higher the religious level of LDII worshipers, the higher the level of family harmony. The author's harmonious family can be drawn from one of Prastowo's families whose religious level is high, so the relationship with all family members becomes very good besides fulfilled all kinds of fundamental needs (biological and physiological),instrumental needs and integrative needs